Typology of Cocoa Seedlings Derived from Orthotropic and Plagiotropic Cuttings Compared with Grafting and Hybrid Seeds - Teguh Iman Santoso; Endang Sulistyaningsih; Eka Tarwaca Susila Putra; Agung Wahyu Susilo (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Cocoa derived from cuttings is expected to overcome the limitations of grafting and hybrid seed propagation. This study aimed to determine the typology of cocoa seedlings derived from cutting, grafting, and hybrid seeds and the similarity among propagations, and assess the biochemical content of budwood cuttings and its relationship with the success rate. This research was conducted at the greenhouse of the Indonesian Coffee and Cocoa Research Institute, East Java, from April to December 2022 by adopting a completely randomized design. A single-factor experiment was performed on propagation methods, namely hybrid seed (HS), orthotropic cutting (OC), plagiotropic cutting (PC), orthotropic grafting (OG), and plagiotropic grafting (PG). The growth characteristics, anatomical characteristics, and biochemical contents of cuttings were observed. Results showed that compared with PC, OC generated a larger root pith diameter that played a role in the improved growth performance. The leaf area, net assimilation rate, and relative growth rate in OC were similar to those in HS. The time to produce OC was similar to PG to meet the minimum standard requirements of ready-to-plant seedlings. However, the root volume, area, and length in OC were below those in HS and still needed to be improved. The cuttings derived from the budwood garden had higher sucrose contents than those from the production garden. Therefore, obtaining OC and PC samples from a budwood garden is recommended to achieve a high success rate.